The ethics of ICT. Transversal competencies and paradox - Marta BURGUET; Mª Rosa BUXARRAIS (Ediciones Universidad de Salamanca, 2013)
Education systems in the era of new technologies have a revolution in traditional learning processes. For proper implementation of these changes, teachers have to be train in 'new' ethical competencies, which give meaning to the digital skills. This leads to a new way of understanding pedagogy where students gain prominence and autonomy to obtain, for themselves, answers to the questions. This kind of pedagogy implemented in the classrooms of both types of competency reveals some paradoxes that education must assume as current and future challenges.